Future virialized structures: an analysis of superstructures in the SDSS-DR7 - Luparello, Heliana Estefanía (2011)
We construct catalogues of present superstructures that, according to a Λ cold dark matter (ΛCDM) scenario, will evolve into isolated, virialized structures in the future. We use a smoothed luminosity density map derived from galaxies in SDSS-DR7, Abazajian et al., data and separate high-luminosity density peaks. The luminosity density map is obtained from a volume-limited sample of galaxies in the spectroscopic galaxy catalogue, within the SDSS-DR7 footprint area and in the redshift range 0.04 < z < 0.12. Other two samples are constructed for calibration and testing purposes, up to z= 0.10 and 0.15. The luminosity of each galaxy is spread using an Epanechnikov kernel of 8Mpch-1 radius, and the map is constructed on a 1Mpch-1 cubic cell grid. Future virialized structures (FVSs) are identified as regions with overdensity above a given threshold, calibrated using a ΛCDM numerical simulation and the criteria presented by Dünner et al. We assume a constant mass-to-luminosity ratio and impose the further condition of a minimum luminosity of 1012L⊙. According to our calibrations with a numerical simulation, these criteria lead to a negligible contamination by less overdense (non-FVS) superstructures. We present a catalogue of superstructures in the SDSS-DR7 area within redshift 0.04 < z < 0.12 and test the reliability of our method by studying different subsamples as well as a mock catalogue. We compute the luminosity and volume distributions of the superstructures, finding that about 10 per cent of the luminosity (mass) will end up in future virialized structures. The fraction of groups and X-ray clusters in these superstructures is higher for groups/clusters of higher mass, suggesting that future cluster mergers will involve the most massive systems. We also analyse known structures in the present Universe and compare with our catalogue of FVSs.